2005
DOI: 10.1159/000088014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Capacity and Preventive Effects of a Topical Emulsion and Its Vehicle Control on the Skin Response to UV Exposure

Abstract: Supplying topical exogenous antioxidants to the skin may prevent or minimize free radical-induced damaging. This study determines antioxidative capacity of a topical skin care emulsion (an oil-in-water vitamin E-containing formulation) versus its vehicle on human skin that was exposed to ultraviolet radiation (UVR) by utilizing a photochemiluminescence device and biophysical methods. Ten healthy Caucasians (3 male and 7 female; mean age 47 ± 10 years) were enrolled. In a randomized and double-blind manner, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 57 publications
0
20
0
1
Order By: Relevance
“…Supplying topical exogenous antioxidants to the skin can prevent or minimize UVB-induced damage [18] . Despite various reports linking many of the beneficial properties of selenium to its use, no comprehensive study has been conducted to investigate the skin absorptive ability of related compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplying topical exogenous antioxidants to the skin can prevent or minimize UVB-induced damage [18] . Despite various reports linking many of the beneficial properties of selenium to its use, no comprehensive study has been conducted to investigate the skin absorptive ability of related compounds.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the complete removal of lipids from the SC led to a 100-fold increase in water permeability [50] . Healthy skin has a slightly acidic pH, and the acidity of the skin maintains antimicrobial activity [18] . Disturbing this naturally acidic mantle may cause skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C kadar güçlü bir antioksidan değildir. Foto hasara karşı ve cildin neminin düzenlenmesi için kullanılmaktadır 42 . Nikotinamid (B3) ile yapılan bir çalışmada transepidermal su kaybının azaldığı ve bu nedenle kronolojik yaşlanmaya karşı kullanılabileceği belirtilmiştir 43 .…”
Section: Kollajen Ve Elastin Ile Bu Yapıları Destekleyen Bileşenlerunclassified
“…All the 4 vitamins may have an antioxidant effect on the stratum corneum [12,[16][17][18][19][20][21][22]. Furthermore, both vitamin A in the precursor form of retinol and in the activated form of retinoic acid and vitamins C and B3 can promote the neosynthesis of collagen in the dermis [16,19,[22][23][24][25][26][27].…”
Section: Open Accessmentioning
confidence: 99%